2018
DOI: 10.1111/jdi.12848
|View full text |Cite
|
Sign up to set email alerts
|

One‐hour oral glucose tolerance test plasma glucose at gestational diabetes diagnosis is a common predictor of the need for insulin therapy in pregnancy and postpartum impaired glucose tolerance

Abstract: Aims/IntroductionGestational diabetes mellitus (GDM) is a risk for adverse perinatal outcomes, and patients with a history of GDM have an increased risk of impaired glucose tolerance (IGT). Here, we carried out two non‐interventional and retrospective studies of GDM patients in Japan.Materials and MethodsIn the first study, we enrolled 529 GDM patients and assessed predictors of the need for insulin therapy. In the second study, we enrolled 185 patients from the first study, and assessed predictors of postpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 38 publications
1
23
1
1
Order By: Relevance
“…Physicians need to establish at the time of diagnosis of GDM whether insulin therapy is required for glycemic control. In previous studies, risk factors for insulin therapy in patients with three abnormal values in the OGTT results were similar to those identified in the present study ( 18 ). However, some patients were treated with insulin even if they had only one abnormal value in a 75-g OGTT result or mild glucose intolerance, making it difficult to identify high-risk GDM on the basis of OGTT results alone.…”
Section: Discussionsupporting
confidence: 91%
“…Physicians need to establish at the time of diagnosis of GDM whether insulin therapy is required for glycemic control. In previous studies, risk factors for insulin therapy in patients with three abnormal values in the OGTT results were similar to those identified in the present study ( 18 ). However, some patients were treated with insulin even if they had only one abnormal value in a 75-g OGTT result or mild glucose intolerance, making it difficult to identify high-risk GDM on the basis of OGTT results alone.…”
Section: Discussionsupporting
confidence: 91%
“…The insulin requirement among our GDM women (8.7%) was low in comparison to other published data (10.8–52.8%) [ 5 , 20 , 21 , 22 , 26 , 27 , 28 ]. Singapore, which has a similar multi-ethnic population to Malaysia, reported a comparable rate to ours (5.6–10.4%) [ 32 ].…”
Section: Discussioncontrasting
confidence: 86%
“…Ares et al found that the two-hour plasma glucose level was significantly higher in the insulin-treated group [ 20 ]. The study, alongside several others, discovered that the post-glucose load abnormalities were significant predictors of insulin requirement among GDM women [ 20 , 21 , 23 , 26 , 27 ]. We found that two-hour glucose derangement was significantly associated with diet therapy and reduced the risk of insulin usage.…”
Section: Discussionmentioning
confidence: 97%
“…Bergman et al [34] reported a longitudinal association of elevated 1-h PG > 8.6 mmol/l (155 mg/dl) with and without impaired glucose tolerance with cumulative incidence of diabetes over 24 years in a non diabetic cohort. In pregnant women too, the need for insulin therapy is higher in those with high 1-h PG values in OGTT [35]. For GDM diagnosis, 1- h PG estimation is recommended by most professional organizations like IADPSG [13], WHO [14] and International Diabetes Federation [36], but has not been included in the NICE diagnostic criteria [12].…”
Section: Discussionmentioning
confidence: 99%